Writer's guide to nursing periodicals - Daly, Jeanette M.; Sage eBooks (Thousand oaks, Calif. ; London : SAGE, 2000)
Jeanette Daly's single volume resource provides specific guidelines for writers who want to contribute to nursing journals. The book features arranged entries for 101 nursing journals by subject area and purpose and focus of each journal.
Specialized.
Description based on print version record.
Includes index.
Keywords: Nursing -- Authorship; Nursing -- Periodicals; Electronic books